A brief history of gangsters - Robb, Brian J. (Running Press Robinson, 2015)
The romanticised American gangster of the Prohibition era has proved an enduringly popular figure. Even today, names like Al Capone and Lucky Luciano still resonate. Robb explores the histories of key figures, from gangs in the Old West, through Prohibition and the Great Depression, to the likes of John Gotti and Frank Lucas in the 1970s and 1980s. He also looks at the gangster in popular culture, in hit TV series such as Boardwalk Empire. Although the focus is strongly on the archetypal American gangster, Robb also examines gangsters around the world, including the infamous Kray twins in London, French crime kingpin Jacques Mesrine, the Mafia Dons of Sicily, and the rise of notorious Serbian and Albanian gangs. Infamous Australian outlaw Ned Kelly makes an appearance, as does Colombian drug lord Pablo Escobar, while other sections provide details of the Chinese Triads and the Yakuza in Japan. Robb also explores the gangster in popular culture, especially in film and television. Recent hit TV series such as The Sopranos and Boardwalk Empire and blockbuster movies like Public Enemies and Gangster Squad show that the gangster is here to stay.